2020
DOI: 10.31557/apjcp.2020.21.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Expression in the Benign Prostatic Hyperplasia and Prostate Cancer Tissues, Relation with Transcription, Growth Factors, Hormone Reception and Components of the AKT/mTOR Signaling Pathway

Abstract: Background: Progesterone receptor (PR) is a critical regulator in reproductive tissues that controls a variety of cellular processes. The objective of the study was to study the PR expression in patients with benign prostatic hyperplasia and prostate cancers in connection with the transcription, growth factors, AR, ERα, ERβ, and components of the AKT/ mTOR signaling pathway expression. Materials and methods: Ninety-seven patients with prostate pathology were enrolled in the study. Forty-two patients had benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Also, another study stated that pazopanib can halt rat liver fibrosis through modulating the pro-inflammatory cytokines TNF-α and IL-6 (Elshal et al 2015 ). Furthermore, a study conducted on patients with renal cell carcinoma revealed that pazopanib reduced the NF-κB p65 level in kidney cancer tissues (Spirina et al 2017 ). NF-κB activation triggers the transcription of β-secretase (Tamagno et al 2012 ) as well as several pro-inflammatory genes such as TNF-α (Lu et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study stated that pazopanib can halt rat liver fibrosis through modulating the pro-inflammatory cytokines TNF-α and IL-6 (Elshal et al 2015 ). Furthermore, a study conducted on patients with renal cell carcinoma revealed that pazopanib reduced the NF-κB p65 level in kidney cancer tissues (Spirina et al 2017 ). NF-κB activation triggers the transcription of β-secretase (Tamagno et al 2012 ) as well as several pro-inflammatory genes such as TNF-α (Lu et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…При многофакторном анализе установлено, что экспрессия РП в опухолевых клетках была независимым негативным прогностическим фактором клинической неудачи лечения РПЖ [30,31]. 2020) обследовали 97 пациентов с опухолевой патологией предстательной железы (42 пациента с ДГПЖ, 55 пациентов с местно-распространенным РПЖ) на предмет оценки уровня экспрессии в клетках опухолевых тканей ядерных факторов NF-κB p65, NF-κB p50, HIF-1, HIF-2, факторов роста VEGF, VEGFR2, CAIX, сигнальных белков Brn-3α, TRIM16, а также андрогеновых рецепторов, ЭР-α, ЭР-β и РП [32]. Результаты показали более выраженную экспрессию РП у пациентов с РПЖ по сравнению с пациентами с ДГПЖ, а уровень его мРНК зависел от экспрессии андрогеновых рецепторов, сигнальных белков Brn-3α и TRIM16, компонентов сигнального пути AKT/mTOR и факторов роста.…”
Section: роль прогестерона в патогенезе заболеваний предстательной же...unclassified
“…Усиление экспрессии РП сопровождалось подавлением активности сигнального каскада андрогеновых рецепторов и уровней мРНК сигнального белка Brn-3α в опухолевых тканях, что сопровождалось снижением уровня экспрессии мРНК ядерных факторов NF-κB, HIF-1 и факторов роста VEGF и VEGFR2. Таким образом, полученные данные свидетельствуют о значимости экспрессии РП в развитии патологии предстательной железы [32].…”
Section: роль прогестерона в патогенезе заболеваний предстательной же...unclassified